2003
DOI: 10.1177/095632020301400104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Pharmacology of D-d4FC, a Nucleoside Analogue Active against Drug-Resistant HIV

Abstract: The backbone of effective highly active antiretroviral therapy regimens for the treatment of HIV infections currently contains at least two nucleosides. Among the features that influence the potency of each component of a regimen and the overall efficacy of the combination are the cellular uptake and bioconversion of nucleoside analogues to their active triphosphate form, and the extent of possible interactions in these steps that might occur when more than one nucleoside is used in a regimen. D-d4FC (Reverset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(68 reference statements)
2
9
0
Order By: Relevance
“…Both enzymatic assay and recombinant RT assay demonstrated similar fold increases in resistance with or without ATP. Thus, these data demonstrated that S68⌬ resulted in resistance to several clinically important nucleoside analogs but remained susceptible to ZDV, thus supporting the previously published cell-based studies (6,9,15,40).…”
Section: Resultssupporting
confidence: 89%
“…Both enzymatic assay and recombinant RT assay demonstrated similar fold increases in resistance with or without ATP. Thus, these data demonstrated that S68⌬ resulted in resistance to several clinically important nucleoside analogs but remained susceptible to ZDV, thus supporting the previously published cell-based studies (6,9,15,40).…”
Section: Resultssupporting
confidence: 89%
“…These findings are consistent with a previous report by Erickson-Viitanen et al and support the hypothesis that enzymes involved in the activation of DFC and 3TC are not rate limiting for the production of their 5Ј-TP metabolites (9). It is likely that this drug interaction occurs at the NTP levels with the HIV RT.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, these studies suggest that although 3TC and DFC are cytidine analogs activated by 2Ј-deoxycytidine kinase, they may be considered for combination therapy for the treatment of HIV infections, although a dose reduction for 3TC may be needed (9,20). It should be noted that FTC, a related nucleoside, is approved at a dose of 200 mg, which is 33% and 50% lower than the approved dose of 3TC for HIV and hepatitis B virus, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cell culture experiments suggested that the antiviral effects of reverset are additive and in some cases synergistic with PIs, NNRTIs and NRTIs [221]. Reverset is active against HIV-1 strains resistant to AZT, 3TC, d4T and tenofovir [218], as well as strains coresistant to AZT and 3TC and several strains bearing double and triple mutations [220].…”
Section: Nucleoside Rt Inhibitors In Clinical Developmentmentioning
confidence: 98%